Human immunodeficiency virus can infect CD4-negative human fibroblastoid cells. - Tateno, M (1989)
Certain human immunodeficiency virus (HIV) strains were shown to infect human fibroblastoid cells. Replication was demonstrated only by coculturing normal peripheral blood mononuclear cells or human T-lymphotropic virus type 1-transformed T-cell lines with the infected human cells. This infection of human fibroblastoid cells did not involve the CD4 molecule and did not have the properties of endocytosis. Human sera could be distinguished by their ability to neutralize HIV infection of the fibroblastoid versus human T-cell lines. These observations demonstrate further that other mechanisms for viral entry, besides CD4 binding, must be considered for HIV. They also indicate the wide cellular host range and heterogeneity of HIV strains. The possibility that fibroblastoid cells serve as a reservoir for the AIDS virus and are involved in connective tissue disorders of infected individuals merits attention.